MOBILE WEB-BASED VILLAGE SERVICE APPLICATION DESIGN WITH EXTREME PROGRAMMING METHODOLOGY - EVA SUSILAWATI; Deri Fikri Fauzi (Sean Institute, 2021)
Information technology is developing very rapidly which affects the business world and the industrial world, including government agencies. Public services in making population documents are an important type of service that must exist in every village. The Center for the Study of Regional Autonomy conducts a study on the quality of village government services, related to this, it is necessary to continuously improve government services, both physical and administrative. One of them is the problems faced by village government agencies, such as the procedures applied are not clear and the service is still manual so that the processing time becomes longer. This study aims to improve the quality of service which it has an impact on services that are less than optimal for the population, it is hoped that with the design of this program it can be better than the manual system, so that it can run more effectively and efficiently. The data collection method used in collecting data in this study is by conducting interviews with various parties, observing, and reviewing the center in order to find reference materials. The design of this information system uses the Agile Development Methods system development method with the extreme programming model.